MXenes for blue energy harvesting - Gwanho Kim; Kaiying Zhao; Shengyou Li; Guangtao Zan; EunAe Shin; Minji Kwon; Cheolmin Park (Communications Materials)
Abstract Blue energy harvesters, which generate renewable energy through interactions with water and moisture, provide innovative solutions for addressing global energy and sustainability demands. Although materials such as graphene-based materials, cellulose, and metal-organic frameworks have been investigated for these devices, their practical application has been hindered by challenges including chemical instability, scalability issues, and fabrication complexity. MXenes, a class of two-dimensional transition metal carbides and nitrides, have emerged as promising candidates for blue energy harvesting. Their exceptional hydrophilicity, tunable surface chemistry, and high electrical conductivity facilitate efficient ion transport and charge transfer processes. These properties render MXenes particularly suitable for integration into various blue energy harvesting systems, including hydrovoltaics, solar steam generators, and osmotic power systems. This review systematically analyzes the mechanisms, material designs, and performance metrics of MXene-based energy devices, emphasizing their significant advantages over conventional materials. Furthermore, it provides insights into the current state of MXene-based blue energy technologies and explores future research directions to enhance their potential as transformative solutions for sustainable energy systems.